2015
DOI: 10.1182/blood-2015-06-650887
|View full text |Cite
|
Sign up to set email alerts
|

Paris-Trousseau thrombocytopenia is phenocopied by the autosomal recessive inheritance of a DNA-binding domain mutation in FLI1

Abstract: Key Points• The platelet defect associated with Paris-Trousseau thrombocytopenia and Jacobsen syndrome is caused by an abnormal transcription factor FLI1.• FLI1 DNA-binding ETS domain mutations cause bleeding disorders with both autosomal dominant and recessive patterns of inheritance.Hemizygous deletion of a variable region on chromosome 11q containing FLI1 causes an inherited platelet-related bleeding disorder in Paris-Trousseau thrombocytopenia and Jacobsen syndrome. These multisystem disorders are also cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 18 publications
4
59
0
Order By: Relevance
“…MPL mRNA levels also correlated with FLI1 mRNA levels ( Figure S2). Surface MPL protein levels in iMegs at days 2 to 5 of differentiation ( Figure 1C) were decreased in the FLI1 +/-and PTSX lines, consistent with reports of decreased MPL after FLI1 mutation 13 and of MPL as a direct target gene of FLI1 35 . MYH10 transcript was increased during iMeg differentiation in the FLI1-low lines, reflecting reports of increased MYH10, silenced during normal megakaryocyte polyploidization and maturation 36 , in PTSx patient platelets 3,13,37 .…”
Section: Establishment and Characterization Of Imegs With Differing Lsupporting
confidence: 88%
See 1 more Smart Citation
“…MPL mRNA levels also correlated with FLI1 mRNA levels ( Figure S2). Surface MPL protein levels in iMegs at days 2 to 5 of differentiation ( Figure 1C) were decreased in the FLI1 +/-and PTSX lines, consistent with reports of decreased MPL after FLI1 mutation 13 and of MPL as a direct target gene of FLI1 35 . MYH10 transcript was increased during iMeg differentiation in the FLI1-low lines, reflecting reports of increased MYH10, silenced during normal megakaryocyte polyploidization and maturation 36 , in PTSx patient platelets 3,13,37 .…”
Section: Establishment and Characterization Of Imegs With Differing Lsupporting
confidence: 88%
“…A single report based on the study of primary marrow cells from two patients with PTSx concluded that the platelet disorder was due to allelic-exclusion expression of FLI1 12 . Recently, point mutations and amino acid substitutions in the DNA-binding domain of FLI1 have been implicated as the probable cause of inherited thrombocytopenia in patients 3,13 . While these reports suggest that FLI1 heterozygous exclusion may be an important cause of inherited thrombocytopenia, they did not detail the platelet defect or compare them to PTSx platelets.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Blood, Kautz et al 1 show that the ablation of the erythroid-derived factor erythroferrone (ERFE), which has been shown to be highly expressed in b-thalassemic mice, 2 restores hepcidin levels and corrects iron overload. However, correction of hepcidin levels in those mice does not improve anemia of b-thalassemia.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Sequencing of FLI1 revealed a homozygous missense mutation at position 970 (c.970C.T) that predicts an arginine to tryptophan substitution in the conserved DNA-binding domain of FLI1. 1 Functional analysis of the c.970C.T mutation by a luciferase reporter assay demonstrated decreased transcriptional activity of known gene targets of FLI1, including GP6, GP9, and ITGA2B, with a concomitant reduction of the respective protein expression in the cell lines as well as in platelets of affected individuals, strongly indicating a role of the FLI1 mutation in the platelet phenotype. As the parents do not show a platelet defect despite being heterozygotes for the c.970C.T mutation, the mechanisms that govern the autosomal dominant thrombocytopenia associated with FLI1 hemizygous deletions are still unclear.…”
mentioning
confidence: 98%
“…6 More recently, missense mutations and deletions in the DNAbinding domain of FLI1 have been implicated as the probable cause of the megakaryocyte/platelet defects observed in patients with PTS. 7,8 Although these reports suggest that FLI1 hemizygous deletion may be an important cause of the inherited thrombocytopenia, they did not detail the platelet defect or compare them with PTS platelets. Mice lacking FLI1 die of embryonic hemorrhage that is attributed to the role of FLI1 in both megakaryopoiesis and endothelium and hemangioblast specification.…”
mentioning
confidence: 99%